KEPUTUSAN NASABAH MENABUNG PADA BANK ACEH SYARIAH CABANG BANDA ACEH - Rafikah Rafikah; Amrusi Amrusi; A Razak (Jurnal Economica Didactica, 2019)
The development of Islamic economics or so-called sharia economy in Indonesia is currently growing so rapidly. The presence of sharia banks in the community considered able to overcome the difficulties that occur when saving in conventional banks. As is well known to conventional banks using interest. While already known also the interest system on the bank classified riba a thing that is forbidden in Islam. As for the formulation of this research problem is 1) What drives the decision of customers to save at Bank Aceh Sharia Branch Banda Aceh? 2) What are the most dominant factors affecting customers to save at Bank Aceh Syariah Branch of Banda Aceh ?. The approach used in this research is quantitative approach with descriptive research type. The techniques used in data collection are library research, field research in the form of observation, documentation and questionnaire.The result of the research indicates that that encourages the decision of customers to save at Bank Aceh Syariah branch of Banda Aceh because it is influenced by several factors ranging from product with a total value of 4.13 average in very high category, profit sharing system with total average value equal 3, 94 in the high category, the service with the same average total of 3.95 in the high category, the promotion with a total grade of 3.56 in the high category, the location with a total average value of 3.92 in the high category and psychological factors with a total grade of 4.05 in very high category. Then the most dominant influence is the product where the product is the first thing that most dominant influence the decision of customer to save at Bank Aceh Syariah branch of Banda Aceh with total value average 4,13 in very high category.